Student Mobility in North African Countries and the Need for an Information System for its Management - Benmoussa, Khaoula; Laaziri, Majida; Khoulji, Samira; Mohamed Larbi, Kerkeb (Transactions on Engineering and Computing Sciences, 2017)
University cooperation is a major concern in North Africa as in the rest of the world. Indeed, the cooperation of the universities of these countries with their counterparts abroad is very active. The number of actions identified for the countries of North Africa is higher than that recorded for the countries of sub-Saharan Africa as a whole. This means that these countries have thirsted for openness to the world and knowledge. Several partnership programs fund cooperation actions with higher education institutions in North Africa and encourage student mobility, which is a source Enrichment for the education system. In North Africa, the mobility of students, researchers and staff constitutes a great wealth for the education system and one of the essential dimensions of the internationalization of higher education. Student mobility is of great importance at the heart of the missions and strategic plans of universities, as an essential criterion to take into account from the point of view of the evolution of the university system. It is seen as a policy instrument that globally links higher education systems and promotes the flow of talent and the development of a highly skilled workforce. Mobility presents crucial issues not only in the academic Also in the education of citizens open to the world and to society. As a result, international mobility is a linguistically and culturally essential experience for students, but it is a discontinuity in their academic curriculum. International mobility is favored by states; it is a wealth both for countries of departure and destination This article analyses the incoming and outgoing mobility of foreign students from and to the countries of North Africa. This mobility is massive; its rate is notoriously one of the highest in the world since the late 1980s. It involves interactions between students and researchers at international level and it is also a vehicle for knowledge exchange and a criterion for developing the potential for research and innovation, and Improvement of the performance of the higher education system in North Africa. This article also provides the basis for a cooperative information system capable of managing the inbound and outbound student mobility flows of these countries.